Firma jako wartość dla przedsiębiorcy - Kamosiński, Sławomir (Annales. Etyka w Życiu Gospodarczym, 2019)
In this paper I propose to show a problem that at first sight seems clear, and thus “non-scientific”; however, after a closer look at the source material, it proves to be an important factor for contemporary entrepreneurs conducting business activities. The scientific issue is encapsulated in a concise statement: the company as a value for the entrepreneur. In order to develop the presented thesis, one must point to the fact that a company that has been established by an entrepreneur has a particular value for him, both in the material sense (its valuation on the market), and in an immaterial sense (as a symbolic value). It seems that the symbolic value greatly exceeds the material value, if we consider the entrepreneur’s perspective. Analysis of the value of a company throughout the research allows us to perceive it as the actual fulfillment of an entrepreneur’s life plans, as a workplace and a family value (frequently called the family gem). The enterprise, which is at the same time a brand, is very often the entrepreneur’s brand certificate. The social involvement of the entrepreneur and the formation of an integrated, loyal team of employees are also values in themselves. Considering the non-material value, the enterprise allows the entrepreneur and the employees to meet their needs of self-realization and appreciation. The paper was prepared based on an analysis of answers entrepreneurs gave to specialist periodicals and popular dailies. In addition, I have used my own research, conducted in 2017, among entrepreneurs who represent the small and medium enterprise sector located in towns and villages.